(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed to identify the impact of organizational silence on institutional excellence through organizational commitment as a mediating variable in the industrial institutions in the King Hussein Bin Talal Development Area. The study population consists of all managers and supervisors in the plants in the King Hussein Bin Talal Development Area in Al-Mafraq Governance, which includes (31) plants. A questionnaire was distributed to a random sample of (135) managers and supervisors. (94) questionnaires were subjected for statistical analysis through SPSS and Amos programs. The study reached several results, the most notable of which are the presence of a statistically significant effect of organizational silence on institutional excellence and the presence of an indirect statistically significant effect of organizational commitment as a mediating variable in the relationship between organizational silence and institutional discrimination. One of the most notable recommendations of the study was to increase the interest of industrial organizations in providing an atmosphere that supports the participation of workers in expressing opinions and suggestions for work and establishing a culture of expression of opinion and freedom to exchange ideas and opinions by factory administrations to be a motivation for workers to participate.